Effects of PEG-induced drought stress on regulation of indole alkaloid biosynthesis in Catharanthusroseus. Issue 1 (1st January 2017) - Liu, Ying; Meng, Qinghuan; Duan, Xihua; Zhang, Zhonghua; Li, Dewen
ABSTRACT: Catharanthus roseus ( C. roseus ) plants were used to investigate the terpenoid indole alkaloids (TIAs) accumulation under the condition of PEG-induced drought stress. Multivariate analysis showed that 35% PEG6000 could induce more obvious and stable accumulation on proline (PRO) content and the relative water content (RWC). The results indicated that there were gradual increase and then decrease ( p  < .05) in the contents of vindoline (VIN) and catharanthine (CAT) under 35% PEG6000 stress, but the content of vinblastine (VBL) increased gradually. In addition, the expression levels of tryptophan decarboxylase (TDC), strictosidine synthase (STR) and deacetylvindoline-4-O-acetyltransferase (DAT) were upregulated in plants under 35% PEG6000 stress. Further correlation analysis indicated that CAT accumulation was significantly correlated with TDC gene expression, and VBL accumulation was significantly correlated with peroxidase ( p  < .05). Our results suggest that the cultivation of C. roseus in drought stress would serve as effective treatment for accumulating TIAs.